Effect Of Results And Inflation On Third Party Funds In Sharia Commercial Banks And Sharia Business Units Period 2011-2020 - Hidayah, Taufiq (International Journal of Science, Technology & Management, 2022)
This study aims to determine the effect of profit sharing and inflation on third party funds in Islamic commercial banks and sharia business units. The tests used in this research are multiple linear regression test, normality test, classical assumption test (multicollinearity test and autocorrelation test), statistical test (coefficient of determination (R2), statistical F test, and statistical t test). The samples of this research are profit sharing statistics and third party funds of Islamic Commercial Banks and Sharia Business Units from January 2011 to December 2020 period and inflation statistics in Indonesia from January 2011 to December 2020. simultaneous profit sharing and inflation of third party funds. And Profit Sharing and Inflation Variables give a joint influence of 17.8 % on the Third Party Funds Variable.